Factors Associated with Anxiety During Menopause in District Housing Samalanga - Safitri, Liza; Manan, Maidar Abdul; Ramadhaniah (International Journal of Applied Research and Sustainable Sciences, 2024)
In 2020 in Indonesia, 14 million menopausal women will reach 7.4% of the total population. Anxiety is a common psychological symptom of menopause. The research aims to determine the factors associated with anxiety during menopause in the Lima Village, Samalanga District. This research is analytical with a cross-sectional approach. The population in the study of women aged 45-59 years in Lima Village was 504. The research sample was 83 people. Data was collected from 01 – 15 June 2023, using a questionnaire through interviews. Data analysis used the Chi-Square test. The research results showed that 76% of respondents experienced low anxiety, 54.2% had secondary education, 51.8% of respondents had less knowledge, 25.3% of respondents' attitudes were negative, 37.3% of respondents stated there was no family support, income did not match the UMP 79.5% and negative self-acceptance 31.3%. The research conclusion is that there is a relationship between knowledge, attitudes, family support, income and self-acceptance, and maternal anxiety during menopause